Citizenfour [videorecording (DVD)] - Poitras, Laura; Poitras, Laura (RADiUS TWC, 2015)
With unprecedented access, this gripping behind-the-scenes chronicle follows award winning director Laura Poitras and journalist Glenn Greenwald's remarkable encounters with whistle-blower Edward Snowden in a hotel room in Hong Kong, as he hands over classified documents that provide evidence of mass indiscriminate and illegal invasions of privacy by the NSA.